The Importance of International Collaboration to Enhance Education for Environmental Citizenship - David Christian Finger; Camelia Draghici; Dana Perniu; Marija Smederevac-Lalic; Rares Halbac-Cotoara-Zamfir; Azra Sehic; Marijana Kapović Solomun (Sustainability, 2021)
Environmental Education is essential to promote awareness and facilitate the development of environmental citizens. To contribute to the enhancement of environmental awareness, Iceland, Serbia, Bosnia and Herzegovina, and Romania have collaborated in joint educational projects which aim at building capacities on sustainable development, delivering environmental teaching lectures, and developing open educational resources. This article presents past and ongoing collaborations between the mentioned countries, assesses the status of environmental education, and highlights the benefits of international collaboration. For this purpose, information on environmental courses in representative universities from each country was collected, SWOT analyses were performed in each country, and a survey among potential students was carried out. The presented analysis reveals that international collaboration raises environmental awareness and increases the likelihood of becoming environmental citizens.